2005
DOI: 10.1016/j.jvs.2004.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Compelling nature of arterial manifestations in Behçet disease

Abstract: Although surgical intervention should be postponed until active inflammation has subsided, often this is not possible, because of the emergent nature of these problems. Most arterial complications of vasculo-Behcet disease present with a pseudoaneurysm rupture or with impending rupture. An aggressive surgical approach can be life-saving in such instances, and should be undertaken regardless of long-term complications, which are more common when the operation is performed in the presence of active inflammation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 13 publications
(16 reference statements)
2
74
0
4
Order By: Relevance
“…Fatal vascular complications are frequent; however, debate about the optimal time point for surgery continues (1). Iscan et al reported a mortality of 2 patients of 34 operations in a total of 20 patients and a 5-year repeat operation-free survival rate of 26% (13). Our findings show that disease activity should be controlled before surgery is performed and immunosuppressive treatment should rather be increased than reduced.…”
Section: Discussionmentioning
confidence: 55%
“…Fatal vascular complications are frequent; however, debate about the optimal time point for surgery continues (1). Iscan et al reported a mortality of 2 patients of 34 operations in a total of 20 patients and a 5-year repeat operation-free survival rate of 26% (13). Our findings show that disease activity should be controlled before surgery is performed and immunosuppressive treatment should rather be increased than reduced.…”
Section: Discussionmentioning
confidence: 55%
“…Patients with Behçet's disease may develop pulmonary involvement in up to 7% of the cases [10]. The most common complication is a pulmonary aneurysm, which in some cases gives rise to massive hemoptysis [11]. Other complications include arterial and venous thromboses, recurrent pneumonia, and arteriobronchial fistulas [12].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombi may develop within the aneurysmal sac, and very rarely distal embolization may occur leading to threatening limb ischemia [74]. The femoral artery is frequently affected.…”
Section: Occlusive Lesionsmentioning
confidence: 99%